(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Pragmalinguistics is a broad field of study. In particular, in the pragmatic linguistic analysis of the newspaper text, it is impossible not to mention its anthropocentric direction in relation to other sectors. According to the system of the state language, the results of the traditional language in the society cannot satisfy the requirements of the communicative- pragmatic system aimed at the implementation of activities on the determination of the national consciousness. Currently, the process of the development of society and its new level of quality requires the determination of the role of language as a cultural mechanism and the improvement of its methodological foundations. This article is devoted to the stages of formation of the newly emerging pragmalinguistics in linguistics, the role and importance of pragmalinguistics.